Office quality classification theoretical and empirical issues - Olayonwa, Ganiyu Onatunde; Iman, Abdul Hamid Mar; Ismail, Suriatini (International Journal of Strategic Property Management, 2012)
Office quality classification literature recognises identification of office classes through division of office market rent distribution into intervals but failed to provide sound theoretical framework and comprehensive empirical approach to this method. This paper theorised that as office rental levels are a function of office quality; high quality office classes should have their mean rents greater than average market rent and mean rents of low quality classes. Also that heterogeneous nature of property coupled with lack of perfect information to market participants could result into differential evaluation of rent and quality of the same property by different market participants. The behaviour of participants normally reflects in distribution of market rent by depicting natural breaks in the distribution that could be captured by univariate data exploration. Frequency and histograms of rent distributions that were assumed to depict the behaviour of market participants were used to divide rent distribution to intervals to identify office quality classes. The results of this classification were validated by discriminant analysis. 67% and 59% accuracies were achieved for estimation and holdout subsamples respectively. This paper extended theoretical and empirical approaches in office quality classification. The proposed empirical approach could be used in future classification research.First Publish Online: 19 Jun 2012